Programs for international medical graduates. - Nasmith, L. (College of Family Physicians of Canada, 1993)
Medical graduates from other countries provide health care in many regions of Canada; yet differences in training standards can cause problems. A recent survey looked at the requirements of provincial licensing bodies and the preresidency programs of Canadian faculties of medicine. Quebec, Ontario, and Manitoba provide such programs, which differ in length, content, and evaluation process. McGill has recently launched a more focused program.